Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: =-8/28-7/28=-15/28
b: \(=\dfrac{-4}{18}+\dfrac{3}{7}\cdot\dfrac{14}{15}=\dfrac{-2}{9}+\dfrac{14}{15}=\dfrac{-10+42}{45}=\dfrac{32}{45}\)
c: \(=\dfrac{-3\cdot5+7\cdot2}{20}\cdot\dfrac{-5}{1}-\dfrac{2}{9}\)
\(=\dfrac{-7}{4}-\dfrac{2}{9}=\dfrac{-63}{36}-\dfrac{8}{36}=-\dfrac{71}{36}\)
b)\(\frac{11}{4}:\left(2.y+\frac{5}{7}\right)=\frac{1}{2}\)
\(\left(2.y+\frac{5}{7}\right)=\frac{11}{4}:\frac{1}{2}\)
\(\left(2.y+\frac{5}{7}\right)=\frac{11}{2}\)
\(2y=\frac{67}{14}\)
\(y=\frac{67}{28}\)
Vậy \(y=\frac{67}{28}\)
\(\frac{11}{4}:\left(2y+\frac{5}{7}\right)=\frac{1}{2}\)
<=> \(\left(2y+\frac{5}{7}\right)=\frac{11}{4}:\frac{1}{2}=\frac{11}{4}.2=\frac{11}{2}\)
<=> \(2y=\frac{11}{2}-\frac{5}{7}=\frac{67}{14}\)
<=> y = 67/28
Chúc bạn làm bài tốt
a) Ta có: 1 + 5 + 6 = 12 ; 2 + 3 + 7 = 12
Vậy 1 + 5 + 6 = 2 + 3 + 7
b) Ta có:\(1^2\)\(+5^2\)\(+6^2\)\(=1+25+36=62\)
\(2^2\)\(+4^2\)\(+7^2\)\(=4+16+49=62\)
\(=>1^2\)\(+5^2\)\(+6^2\)\(=2^2\)\(+3^2\)\(+7^2\)
c) Ta có 1 + 6 +8 = 15; 2 + 4 + 9 = 15
Vậy 1 + 6 + 8 = 2 + 4 + 9
\(d,1^2\)\(+6^2\)\(+8^2\)\(=1+36+64=101\)
\(2^2\)\(+4^2\)\(+9^2\)\(=4+16+81=101\)
\(1^2\)\(+6^2\)\(+8^2\)\(=2^2\)\(+4^2\)\(+9^2\)
\(8-12x+6x^2-x^3\)
\(=\left(2-x\right)^3\)
\(125x^3-75x^2+15x-1\)
\(=\left(5x-1\right)^3\)
\(x^2-xz-9y^2+3yz\)
\(=\left(x-3y\right)\left(x+3y\right)-z\left(x-3y\right)\)
\(=\left(x-3y\right)\left(x+3y-z\right)\)
\(x^3-x^2-5x+125\)
\(=\left(x+5\right)\left(x^2-5x+25\right)-x\left(x+5\right)\)
\(=\left(x+5\right)\left(x^2-5x+25-x\right)\)
\(=\left(x+5\right)\left(x^2-6x+25\right)\)
\(x^3+2x^2-6x-27\)
\(=x^3+5x^2+9x-3x^2-15x-27\)
\(=x\left(x^2+5x+9\right)-3\left(x^2+5x+9\right)\)
\(=\left(x-3\right)\left(x^2+5x+9\right)\)
\(12x^3+4x^2-27x-9\)
\(=4x^2\left(3x+1\right)-9\left(3x+1\right)\)
\(=\left(3x+1\right)\left(4x^2-9\right)\)
\(=\left(3x+1\right)\left(2x-3\right)\left(2x+3\right)\)
\(4x^4+4x^3-x^2-x\)
\(=4x^3\left(x+1\right)-x\left(x+1\right)\)
\(=x\left(x+1\right)\left(4x^2-1\right)\)
\(=x\left(x+1\right)\left(2x-1\right)\left(2x+1\right)\)
\(\left(y+\frac{1}{5}\right).\frac{3}{7}=\frac{5}{14}\)
\(\left(y+\frac{1}{5}\right)=\frac{5}{14}:\frac{3}{7}\)
\(\left(y+\frac{1}{5}\right)=\frac{5}{6}\)
\(y=\frac{5}{6}-\frac{1}{5}\)
\(y=\frac{19}{30}\)
Vậy \(y=\frac{19}{30}\)
(y + 1/5) . 3/7 = 5/14
y + 1/5 = 5/14 : 3/7
y + 1/5 = 5/6
y = 5/6 - 1/5
y = 19/30
Chúc bạn học tốt ^^